Establishing ecological justice in the governance of land inventory, ownership, and utilisation in Indonesia - Basuki, Agung; Zaid, M; Mohamed Musa , Alnour Abobaker (Journal of Law, Environmental and Justice, 2023)
This study analyses ecological justice in Inventory, Tenure, Ownership, Use, and Utilisation of Land (IP4T) governance as required by TAP MPR IX/2001 and Government Regulation No. 16/2004 on Land Administration. This study uses a normative legal research technique with legislative and conceptual approaches. According to the author's study, ecological justice is included in IP4T legislation in TAP MPR IX/2001 and Government Act 16 of 2004 on Land Development. The rules of the two legal instruments promote ecological justice, sustainable development, and damage prevention. Article 23 of Government Regulation No. 16/2004 requires all Spatial and Regional Plans to include the IP4T map. This map goes beyond land ownership, use, and utilization. The IP4T dataset also assesses land capabilities and evaluation, including ecological features of the land. Thus, a region's Spatial and Regional Plan must remove IP4T data on land tenure, use, evaluation, and capabilities. Article 3, Article 5, and Article 6 Paragraph (2) of TAP MPR IX/2001 define ecological justice. In practice, these discrepancies impede ecological justice. These inconsistencies are rampant in implementing IP4T (Integrating Principles for Transition) in the mining industry.